2020
DOI: 10.3390/foods9081042
|View full text |Cite
|
Sign up to set email alerts
|

Osmodehydrofreezing: An Integrated Process for Food Preservation during Frozen Storage

Abstract: Osmodehydrofreezing (ODF), a combined preservation process where osmotic dehydration is applied prior to freezing, achieves several advantages, especially in plant tissues, sensitive to freezing. OD pre-treatment can lead to the selective impregnation of solutes with special characteristics that reduce the freezing time and improve the quality and stability of frozen foods. ODF research has extensively focused on the effect of the osmotic process conditions (e.g., temperature, duration/composition/concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 107 publications
0
16
0
Order By: Relevance
“…Sucrose (the most utilized carbohydrate) [155], glucose [156], sorbitol [157], maltose [158], NaCl [159] have been employed as common hypertonic solutes in osmotic dehydration. Temperature, process time, composition, and concentration of the hypertonic solutes are the main useful parameters in osmo-dehydro-freezing [154]. As stated in [160], sucrose showed higher firmness in both 3 and 60 days of storage time than maltitol and trehalose.…”
Section: Osmo-dehydro-freezingmentioning
confidence: 89%
See 1 more Smart Citation
“…Sucrose (the most utilized carbohydrate) [155], glucose [156], sorbitol [157], maltose [158], NaCl [159] have been employed as common hypertonic solutes in osmotic dehydration. Temperature, process time, composition, and concentration of the hypertonic solutes are the main useful parameters in osmo-dehydro-freezing [154]. As stated in [160], sucrose showed higher firmness in both 3 and 60 days of storage time than maltitol and trehalose.…”
Section: Osmo-dehydro-freezingmentioning
confidence: 89%
“…Osmotic dehydration is a proper way to decrease moisture content, leading to easier freezing. Osmo-dehydro-freezing is an integrated process, consisting of two separate stages, including osmotic dehydration and subsequently freezing [8,154]. Compared with air drying (as a pretreatment for freezing), osmotic dehydration need less energy [84].…”
Section: Osmo-dehydro-freezingmentioning
confidence: 99%
“…De Ancos et al (2000) reported that during freezing cell damages to the fruit resulted in the release of vitamin C in raspberries. Giannakourou et al (2020) mentioned that osmodehydrofreezing process with a mixture of sucrose/glucose/ fructose significantly decreased vitamin C owing to a mild leakage of water-soluble compounds out of the cell tissue.…”
Section: N I T I a L 1 Ma S 2 M As 3 M Asmentioning
confidence: 99%
“…Because irradiation does not heat the treated material, the food keeps its freshness and its physical state (frozen or dried commodities; Li et al, 2016). Food irradiation technology is applied to reduce postharvest losses (physical, physiological, mechanical, and hygienic conditions) and control the microorganisms while preserving the product nutritional value (Baeghbali, Ngadi, & Niakousari, 2020; Giannakourou, Dermesonlouoglou, & Taoukis, 2020). Also, Food irradiation (the application of ionizing radiation to food) is a technology that improves the safety and extends the shelf life of foods by reducing or eliminating microorganisms and insects.…”
Section: Introductionmentioning
confidence: 99%